Urgensi Religiusitas dan Resiliensi Akademik dalam Mencegah Drop out Mahasiswa PAI di STIT Al-Khairiyah Cilegon - Aslihah; Wasehudin, Wasehudin; Hadiyyin, Ikhwan; Yuyun Rohmatul Uyuni, Yuyun; Enung Nugraha, Enung (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
The dropout rate of final year students continues to occur until now, a report from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in 2023 noted that as many as 352,494 students in Indonesia dropped out of college or dropped out (DO). around 4.52% of the total students in Indonesia. This can be influenced by several factors, including low academic ability, financial factors, place of residence while studying, place of origin and other factors. Based on this background, the purpose of this study was to analyze the urgency of religiosity and academic resilience in preventing dropout of PAI students at STIT Al-Khairiyah Cilegon and to determine the advantages and disadvantages of religiosity and academic resilience of PAI students at STIT Al-Khairiyah Cilegon. The method used is qualitative with data collection techniques, namely interviews, observation, and documentation. The data sources obtained in this study came from eight informants, four informants from final year students and four informants from alumni of the PAI study program at STIT Al-Khairiyah Cilegon. The results of this study indicate that: First, the religiosity of PAI students at STIT Al-Khairiyah Cilegon plays an important role in forming their academic resilience.